Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/bios11080276
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Droplet Platform for Exploring the Mechanism of Mixed Field Agglutination in B3 Subtype

Abstract: B3 is the most common subtype of blood group B in the Taiwanese population, and most of the B3 individuals in the Taiwanese population have the IVS3 + 5 G > A (rs55852701) gene variation. Additionally, a typical mixed field agglutination is observed when the B3 subtype is tested with anti-B antibody or anti-AB antibody. The molecular biology of the gene variation in the B3 subtype has been identified, however, the mechanism of the mixed field agglutination caused by the type B3 blood samples is still unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Not only the image observation as a quantitative result but also the naked-eye qualitative criteria requiring no prior experience could identify the blood agglutination on the chip. According to some studies, observing blood agglutination on a chip requires only quantitative results from skilled operators [23][24][25]. The naked-eye observation is an important interpretation because it is the first step to screening blood typing results.…”
Section: Image Observation Of Blood Agglutinationmentioning
confidence: 99%
“…Not only the image observation as a quantitative result but also the naked-eye qualitative criteria requiring no prior experience could identify the blood agglutination on the chip. According to some studies, observing blood agglutination on a chip requires only quantitative results from skilled operators [23][24][25]. The naked-eye observation is an important interpretation because it is the first step to screening blood typing results.…”
Section: Image Observation Of Blood Agglutinationmentioning
confidence: 99%
“…Furthermore, a digital microfluidic device with droplet manipulation was used for blood agglutination assays [ 37 ]. Moreover, the current study group utilized a similar concept to study the mechanism of mixed-field agglutination in subtypes [ 38 ]. These studies showed the potential of the microdroplet platform for blood typing.…”
Section: Introductionmentioning
confidence: 99%